The guest book : a novel - Blake, Sarah (Poet) (New York : Flatiron Books, 2019)
"A novel about past mistakes and betrayals that ripple throughout generations, The Guest Book examines not just a privileged American family, but a privileged America. It is a literary triumph. The Guest Book follows three generations of a powerful American family, a family that "used to run the world." And when the novel begins in 1935, they still do. Kitty and Ogden Milton appear to have everything--perfect children, good looks, a love everyone envies. But after a tragedy befalls them, Ogden tries to bring Kitty back to life by purchasing an island in Maine. That island, and its house, come to define and burnish the Milton family, year after year after year. And it is there that Kitty issues a refusal that will haunt her till the day she dies. In 1959 a young Jewish man, Len Levy, will get a job in Ogden's bank and earn the admiration of Ogden and one of his daughters, but the scorn of everyone else. Len's best friend, Reg Pauling, has always been the only black man in the room--at Harvard, at work, and finally at the Miltons' island in Maine. An island that, at the dawn of the twenty-first century, this last generation doesn't have the money to keep. When Kitty's granddaughter hears that she and her cousins might be forced to sell it, and when her husband brings back disturbing evidence about her grandfather's past, she realizes she is on the verge of finally understanding the silences that seemed to hover just below the surface of her family all her life. An ambitious novel that weaves the American past with its present, Sarah Blake's The Guest Book looks at the racism and power that has been systemically embedded in the U.S. for generations" --